2017
DOI: 10.1002/uog.15943
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and long‐term outcomes in fetuses diagnosed with isolated unilateral ventriculomegaly: systematic review and meta‐analysis

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 30 publications
2
41
2
1
Order By: Relevance
“…Several studies suggest an association between the severity of ventriculomegaly and poor outcome. In this study, we found no statistical difference in atrial width when comparing children with and those without a neurodevelopmental disorder.…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies suggest an association between the severity of ventriculomegaly and poor outcome. In this study, we found no statistical difference in atrial width when comparing children with and those without a neurodevelopmental disorder.…”
Section: Discussioncontrasting
confidence: 71%
“…This investigation has only recently become available in clinical practice and may not have been available for the series included in this review. Also, fetal MRI is able to diagnose additional brain abnormalities in 5% of cases 33 , but only in the last decade has it been introduced gradually as an additional fetal central nervous system investigation. Some of the apparently isolated cases may no longer have been classified as isolated had they undergone chromosomal microarray analysis, fetal MRI or appropriate neurosonography according to the current standard guidelines (International Society of Ultrasound in Obstetrics and Gynecology guidelines) 2 .…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The etiology of VM is complex, including obstruction of cerebrospinal fluid flow, focal or generalized brain volume loss, and deformities secondary to the CNS. 9 Due to variations in classification criteria, followup time, and evaluation methods of VM, there is no consensus on appropriate prognostic evaluation of fetuses. Furthermore, research has typically focused on the associated deformities of fetuses after birth, rather than neurodevelopmental retardation.…”
Section: Discussionmentioning
confidence: 99%